A Research Map of Technology-Based Digital e-CRM: A Bibliometric Analysis to Identify Innovations and Future Trends - Lestari, Fitrina; Rahayu, Agus; Hendrayati, Heny (Ilomata International Journal of Management, 2025)
This research investigates the progression of technology-driven digital e-CRM systems, focusing on three primary goals: uncovering research patterns, assessing the impact of technological advancements on e-CRM growth, and identifying future research prospects. The study also seeks to confirm hypotheses regarding the increasing emphasis on technology in e-CRM, the transformative effects of merging e-CRM with e-commerce and digital marketing, and emerging opportunities in analytics, and data security. A bibliometric examination of Scopus-indexed publications was performed using vosviewer application. The datasets were refined through three queries related to e-CRM concepts, technological innovations, and customer outcomes, resulting in 623, 60, and 14 documents, respectively. The results unveil significant trends, including the incorporation of Big Data and predictive analytics for data-informed decision-making, the implementation of AI and machine learning for customization and automation, the integration of social media into CRM strategies to boost engagement, the synergy between e-CRM, e-commerce, and digital marketing for omnichannel experiences, and the shift towards scalable cloud-based CRM systems. These findings validate the hypotheses, underscoring the crucial role of technological progress in reshaping e-CRM and enhancing customer experiences. Future research opportunities encompass advancing sentiment analysis for social media, harnessing IoT for real-time engagement, and tackling data privacy challenges to foster trust. Although limited to bibliometric methods and Scopus data, this study contributes to the existing literature by mapping e-CRM research trends, offering practical insights for professionals, and suggesting future directions aligned with emerging technologies and global challenges, thus emphasizing the strategic importance of aligning e-CRM innovation with evolving consumer needs.